2022
DOI: 10.1115/1.4056337
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Bench-Scale Study on Cuttings-Bed Erosion in Horizontal Wells

Abstract: Cuttings-beds formation while drilling wellbores is a common challenge, especially for horizontal wells, as drilled particles have higher area to be deposited and form cuttings-beds, which can cause several problems such as, increased torque and drag, pipe sticking or pipe breakage, among others. Removal of the drilled-cuttings is done by circulating a suitable drilling fluid through the wellbore. This paper presents results from laboratory tests with deposited cuttings-bed and the flow of a fluid to erode the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Three outcomes were measured: erodibility of the cutting bed, shear rates of different types of fluids, and flow rate dependency along the dune extent. The results showed that the cutting bed is eroded by dune movement [52]. Shirangi et al (2022) developed a new digital-twin methodology for predicting drilling fluid properties to perform real-time calculations for hole cleaning by combining several models, using the large amount of offset data integrated in the model [53].…”
Section: Status Of Hole-cleaning Modelsmentioning
confidence: 99%
“…Three outcomes were measured: erodibility of the cutting bed, shear rates of different types of fluids, and flow rate dependency along the dune extent. The results showed that the cutting bed is eroded by dune movement [52]. Shirangi et al (2022) developed a new digital-twin methodology for predicting drilling fluid properties to perform real-time calculations for hole cleaning by combining several models, using the large amount of offset data integrated in the model [53].…”
Section: Status Of Hole-cleaning Modelsmentioning
confidence: 99%